ANALISIS PERBEDAAN PENDAPATAN SEBELUM DAN SESUDAH PENERAPAN POINT OF SALES (POS) KASIH BERSIH DI AKUCUCI LAUNDRY - Muhlis Muhlis; Muchammad Hamdani; Syaiful Anwar; Mulyani Mulyani (Economicus : Jurnal Ekonomi dan Manajemen, 2025)
The current boom in laundry businesses requires laundry entrepreneurs to always look for strategies to survive. Not only the number of competitors, but also internal problems such as operational problems cause many laundries to only survive for one year. In an effort to improve the efficiency, accuracy and quality of laundry services, many laundry businesses have begun to adopt Point of Sales (POS) technology as a solution to overcome operational problems. This study is to analyze the difference in income before and after the implementation of the Point of Sales (POS) system in the laundry. The sampling method uses purpose sampling techniques with certain criteria, where the only laundry that meets the criteria is Akucuci Laundry. Data collection is carried out through primary and secondary data, while data analysis uses normality tests and paired sample t-tests. The results of the study showed a significant increase in income after the implementation of POS at Akucuci Laundry. The practical implication is that the implementation of technology such as POS can improve operational efficiency and profitability of laundry businesses. In conclusion, the use of POS has a positive impact on Akucuci Laundry's revenue, which provides an incentive for laundry entrepreneurs to consider integrating technology into their operations.